Increasing Access to Agricultural Credit : The Heterogeneous Effects of Collective Action (2020)
Collective action allows individuals to overcome market and state failures, something particularly relevant in rural areas and highly imperfect markets such as agricultural credit. We analyze data on over 2.3 million rural producers in Colombia, as well as on an original subnational database with over 15,000 municipality-year observations, to explore the relation between collective action and access to agricultural credit. We focus on collective action in the form of Rural Producer Organizations (RPOs), and find that it increases the likelihood of an individual accessing agricultural credit, as well as access to credit at the aggregate (municipal) level; that is, there is a positive general equilibrium effect, rather than a crowding-out of credit between RPO members and non-members. These effects are heterogeneous according to the type of credit (source and size). For small farmers, the aggregate positive effect operates only via access to public credit. For large farmers the effect is also positive, but this time via private credit only. Medium-scale farmers, by contrast, see no aggregate increases in credit access. Heterogeneity appears driven by structural segmentation in the credit market across farmer type and source, which is replicated rather than counteracted by the collective action effect. Hence the potential impact of collective action on development outcomes is dependent on contextual conditions.